Railway Express, A Century of Service, 1839-1939
This dramatic painting by a famous artist pictures the 100 colorful years of express service. It contrasts yesterday's romantic Pony Express, the rumbling Overland Stage and quaint "Iron Horse" with today's mighty express trains and super-swift planes that carry the goods of the nation from coast to coast, border to border. Today Railway Express has more than 57,000 employees, 11,300 motor vehicles and 23,000 nation-wide offices, with pick-up and delivery service in all cities and principal towns.